Manajemen Perencanaan Pembelajaran Bahasa Arab Berbasis Kurikulum 2013 Pada SMAN 1 Aceh Barat - Tarmizi Ninoersy; Tabrani ZA; Najmul Wathan (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2019)
Language is a very interesting object to talk about. Until now experts have never finished talking about it. In the context of language, students are expected to be able to understand the meaning of ideas (ideational functions), namely the function of language to express or construct ideas or information that they hear. West Aceh High School 1 is one of the Upper Middle School in West Aceh Regency which in the process of teaching and learning activities also provides one subject of local content, namely Arabic. Based on the results of the study realized by the existence of several significant things in realizing the implementation of learning that leads to the effectiveness of learning to improve the quality of learning. Planning and implementation of Curriculum 2013-based Arabic language learning at SMAN 1 West Aceh contributes discourse and achievements in moving to school autonomy in following the development of globalization that is increasingly evident. The first step in the form of planning and implementing Arabic learning in this school is that with the positioning of Arabic language subjects in the curriculum as a curricular goal in Arabic learning programs. Hierarchically, these Arabic subjects include local content subjects that must be accepted by West Aceh 1 High School students. So that the standard of Arabic Language competency is determined by the school based on its needs by not denying the content standards according to the applicable National Education Standards. The effectiveness includes processes and results. With regard to effectiveness in this process the school has been quite good in fulfilling the 2013 curriculum standards applied in learning Arabic in SMAN 1 Aceh Barat